2018
DOI: 10.1038/s41598-018-25900-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and transcriptome analysis in periocular Sebaceous Gland Carcinoma

Abstract: Sebaceous gland carcinoma (SGC) is a rare, but life-threatening condition with a predilection for the periocular region. Eyelid SGC can be broadly categorised into two subtypes, namely either nodular or pagetoid with the latter being more aggressive and requiring radical excision to save life. We have identified key altered microRNAs (miRNA) involved in SGC shared by both subtypes, hsa-miR-34a-5p and hsa-miR-16-5p. However, their gene targets BCL2 and MYC were differentially expressed with both overexpressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…In the first, Bhardwaj et al ( 28 ) showed that underexpression of miR-200c and miR-141 were correlated with clinicopathological parameters in SGC, but in our present study we did not observe the downregulation of either of these miRNAs. In the second, Bladen et al ( 29 ) demonstrated miRNA expression profiles of SGC using miRNA arrays with 800 probe sets and identified overexpression of miR-16-5p and miR-34a-5p, which were downregulated in the present study. These inconsistencies might be attributable to the control samples used in each experiment: the previous studies used normal tissues (adjacent normal epidermis and tarsal plate) as the control samples while we used sebaceous adenoma.…”
Section: Discussionsupporting
confidence: 58%
“…In the first, Bhardwaj et al ( 28 ) showed that underexpression of miR-200c and miR-141 were correlated with clinicopathological parameters in SGC, but in our present study we did not observe the downregulation of either of these miRNAs. In the second, Bladen et al ( 29 ) demonstrated miRNA expression profiles of SGC using miRNA arrays with 800 probe sets and identified overexpression of miR-16-5p and miR-34a-5p, which were downregulated in the present study. These inconsistencies might be attributable to the control samples used in each experiment: the previous studies used normal tissues (adjacent normal epidermis and tarsal plate) as the control samples while we used sebaceous adenoma.…”
Section: Discussionsupporting
confidence: 58%
“…One previous study reported aberrant immunolabeling, potentially corresponding to TP53 mutations in 19/29 (66%) of OA sebaceous carcinomas; in another series, TP53 mutations were detected in 23/31 (71%) of cases [11,35]. Additionally, overexpression of Has-miR-34a, part of the TP53 suppressor complex, has been reported in both nodular and pagetoid sebaceous carcinomas, and nuclear expression has been observed in 68% of intraepithelial tumor cells in OA cases [10,22]. RB1 mutations were reported in 14/29 (48%) and 12/31 (39%) of OA tumors in two studies [11,35].…”
Section: Discussionmentioning
confidence: 95%
“…[9] However, several studies have identified mutations in tumor suppressor genes, including TP53 and RB1, and p16 expression has been implicated as a robust immunohistochemical marker for these tumors [10][11][12][13][14][15][16][17][18][19]. High-risk human papillomavirus (HPV), whose oncogenes encode well-characterized inhibitors of p53 and Rb, has been detected in up to 18% of OA sebaceous carcinomas without concurrent tumor suppressor mutations, and additional studies have demonstrated overexpression of miRNAs that influence the p53 suppressor complex [6,11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, few studies have been performed at the RNA level and although some novel aberrant miRNAs and IncRNAs have been suggested to play a role this landscape is yet to be fully explored . Large scale molecular studies will help to elucidate the role of germline and somatic variations in the disease pathogenesis.…”
Section: Genetic and Molecular Pathology Findings In Sebaceous Tumoursmentioning
confidence: 99%